IC 9396 The Essential Role Of Human Factors In Advanced Technology - Richard S. Fowkes (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Advanced technology, including automation and computerized information systems, is being adopted in mining at an ever-increasing rate to improve safety and productivity and to decrease overall costs. This U.S. Bureau of Mines report focuses on the human factors issues related to advanced technology. Among the significant facts discovered were the following: Experts studying tile design adoption, and implementation of new technology have stated repeatedly that human factors specialists should be involved from the early planning stages, through design and fabrication, and up to and during production, since human factors has been consistently identified as the biggest obstacle to the efficient utilization of new technology. Also, middle management is generally the greatest obstacle to the adoption of advanced technology, this technology can give rise to worker alienation, boredom, stress, job insecurity, and a sense of isolation; training most of the present work force is more cost effective than hiring new workers; workers are willing to accept new technology if they are given a voice in its implementation; the social and the technical systems should be jointly optimized; and with the intro¬duction of advanced technology, the cognitive or mental, rather than the physical, aspects of human-machine interaction must be emphasized.